Las musas de principio del Siglo XXI: indicios del cambio educativo museal / Muses of the XXI Century: evidence of educational change in museums - Keilyn Rodríguez Sánchez (Universidad de Costa Rica, 2012)
Este ensayo expone que la audiencia es el punto de partida para identificar la mejor manera de diseñar experiencias sensoriales de entretenimiento o educación, es el objeto de la investigación museal, sus gustos e intereses se constituye en el eje de los estudios y de las campañas de mercado. Todo el quehacer museal se orienta a satisfacer los gustos y necesidades del sujeto-visitante para así atraerlo al Museo. Este nuevo enfoque museológico tiene el riesgo de olvidar el objeto en el proceso educativo y centrarse en el sujeto. Se propone la promoción del diálogo sujeto-objeto para que la función educativa del Museo contribuya a la conformación de una sociedad con conciencia histórica-cultural clara. Se concluye que, en las primeras décadas del Siglo XXI los diferentes enfoques de la sociomuselogía, la museografía interactiva, la museología crítica y dialógica, así como los ejes de cambio generados por las innovaciones tecnológicas, las dinámicas de consumo y las comunidades de aprendizaje, apuntan a que la audiencia es el centro de atención, y no el objeto y la forma de ser expuesto como lo fue en el Siglo XX.   This paper presents an allegory between the muses of Greek mythology as the inspiration of memory, knowledge and the arts and the role of muses in inspiring current museum's tasks in the twenty-first century on the worldwide stage, in order to systematize the emerging museological XXI century currents and the central axes of change that are developing in this period. It concludes that in this century different museological approaches to sociomuseology, interactive museography and critical dialogical museology as well as the axes of change generated by technological innovations, the dynamics of consumption and learning communities, suggest that the individual visitor is the main target, and not the object and how it is exhibited (as in the last century). Thus, the individual visitor is the starting point for identifying the best way to design sensory experiences of entertainment or education, he/she is the subject of museum research, his/her likes and interests are the axis of the studies and marketing campaigns. All of the museum's focus is focused on how to satisfy the tastes and needs of the subject, and attract visitors to the Museum. This new approach has the museological risk of forgetting the object in the educational process and instead focusing on the subject. It proposes the encouragement of subject-object dialogue so that the Museum's educational function contributes to the shaping of society with clear cultural and historical awareness.